2016
DOI: 10.1016/j.ajodo.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

How long does treatment with fixed orthodontic appliances last? A systematic review

Abstract: Based on prospective studies carried out in university settings, comprehensive orthodontic treatment on average requires less than 2 years to complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
117
1
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(145 citation statements)
references
References 45 publications
11
117
1
16
Order By: Relevance
“…Mean OT duration was similar for both groups and is in agreement with the findings of a recent review article, where the average comprehensive OT time was 20 months (Tsichlaki, Chin, Pandis, & Fleming, 2016). Based on the results of the present trial, total treatment time was significantly longer for the control group patients (Table 5).…”
Section: Main Findingssupporting
confidence: 92%
“…Mean OT duration was similar for both groups and is in agreement with the findings of a recent review article, where the average comprehensive OT time was 20 months (Tsichlaki, Chin, Pandis, & Fleming, 2016). Based on the results of the present trial, total treatment time was significantly longer for the control group patients (Table 5).…”
Section: Main Findingssupporting
confidence: 92%
“…While fluoride-releasing materials were shown to be rechargeable, no rechargeable CaP resins had been reported. The average orthodontic treatment time ranges 14–33 months28; therefore, Ca and P ion releases lasting much longer than weeks are needed. Recently, novel rechargeable ACP-containing dental resins were developed for the first time, using monomers of pyromellitic glycerol dimethacrylate (PMGDM) and ethoxylated bisphenol A dimethacrylate (EBPADMA) in combination with fillers of ACP.…”
mentioning
confidence: 99%
“…In our patient, treatment was completed in 13 months, which was markedly shorter than usual extraction treatments (13,14). It was previously reported that boys with ASD have a lower bone mineral density than controls (15).…”
Section: Discussionmentioning
confidence: 70%